Impact of Having a Planned Additional Operation at Time of Liver Transplant on Graft and Patient Outcomes - Shirin Salimi (Journal of Clinical Medicine, 2020)
Advances in liver transplantation (LT) have allowed for expanded indications and increased surgical complexity. In select cases, additional surgery may be performed at time of LT rather than prior to LT due to the significant risks associated with advanced liver disease. We retrospectively studied the characteristics and outcomes of patients who underwent an additional planned abdominal or cardiac operation at time of LT between 2011−2019. An additional operation (LT+) was defined as a planned operation performed under the same anesthetic as the LT but not directly related to the LT. In total, 547 patients were included in the study, of which 20 underwent LT+ (4%). Additional operations included 10 gastrointestinal, 5 splenic, 3 cardiac, and 2 other abdominal operations. Baseline characteristics between LT and LT+ groups were similar. The median total operating time was significantly longer in LT+ compared to LT only (451 vs. 355 min, p = 0.002). Graft and patient survival, intraoperative blood loss, transfusion of blood products, length of hospital stay, and post-operative complications were not significantly different between groups. In carefully selected patients undergoing LT, certain additional operations performed at the same time appear to be safe with equivalent short-term outcomes and liver graft survival as those undergoing LT alone